2021
DOI: 10.3390/min11020158
|View full text |Cite
|
Sign up to set email alerts
|

Natural and Anthropogenic Origin of Metals in Lacustrine Sediments; Assessment and Consequences—A Case Study of Wigry Lake (Poland)

Abstract: The contamination of aquatic sediments by metals is a worldwide phenomenon and its assessment is a fairly complex issue, as numerous factors affect the distribution of particular contaminants in the environment, as well as their bioavailability. Wigry Lake, as the object of this study, is almost a perfect water body for such considerations. It has been well investigated and densely sampled (up to 459 sediment samples). The quantities of seven metals were determined using the atomic absorption spectrometry (AAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 93 publications
(172 reference statements)
0
7
0
Order By: Relevance
“…One of the most important roles in water environments is performed by sediments, as they are usually the main collector of contaminants and pollutants introduced into water systems-substances dissolved in water are bonded on the solid particles over time and finally trapped in bottom deposits [24]. Aquatic sediments are also a very dynamic component, in which physico-chemical processes such as transport, diagenesis, bioturbation, remobilization or bioaccumulation, constantly take place [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most important roles in water environments is performed by sediments, as they are usually the main collector of contaminants and pollutants introduced into water systems-substances dissolved in water are bonded on the solid particles over time and finally trapped in bottom deposits [24]. Aquatic sediments are also a very dynamic component, in which physico-chemical processes such as transport, diagenesis, bioturbation, remobilization or bioaccumulation, constantly take place [25].…”
Section: Introductionmentioning
confidence: 99%
“…The physicochemical composition of river sediments in non-industrialised areas depends mainly on the geological structure of the catchment, the dynamics of weathering processes, the morphological structure of the river bed and on the surrounding vegetation [26,27], while in the case of densely populated, urbanised or industrialised catchments, the chemical composition of river sediments reflects the local anthropopressure [28], which may lead to the contamination or pollution of sediments with various substances. Contamination is understood as the increased concentration level of a given chemical in relation to the geochemical background, while pollution means that this concentration poses a threat to biota [24,29]. A distinct, and quite complicated issue, is the appropriate determination of the geochemical background used in environmental risk assessment [30], which may significantly affect the data analysis results [31].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting, however, that these sediments are more finegrained and lighter in color (which is related to the organic matter content). Additionally, research related to seven metals (Cd, Cr, Cu, Fe, Mn, Pb, and Zn) present in Wigry Lake sediments [41,42,64,102,151] has revealed that mean element concentrations in organic gyttja and carbonate gyttja do not differ significantly (except for iron, and to a lesser extent manganese). This may suggest that organic gyttja is genetically more related to carbonate gyttja than to fluvial-lacustrine sediment, although the small amount of organic gyttja samples being studied prevents an unambiguous conclusion.…”
Section: Fluvial-lacustrine Sediment and Organic Gyttjamentioning
confidence: 99%
“…More contemporary adverse changes in the Wigry Lake environment are a result of the urban and industrial development of the nearby city of Suwałki (which held the status of the voivodeship capital in the years 1974-1999) [16,173], the development of tourism [16,174], and the relatively large load of nutrients (especially phosphorus) carried by the Czarna Ha ńcza River [37,91,164,[175][176][177][178], as well as some other contaminants like polynuclear aromatic hydrocarbons [179] or metals, which have been extensively studied [41,42,64,102,147,[149][150][151]163,[180][181][182][183][184][185][186][187]. The analysis of long sediment cores [150,186] revealed that relatively high metal concentrations in the bottom part of profiles originate from crystalline rocks derived from glacial sediments, whereas the middle parts of cores are very pure, and the concentration of metals is higher in the upper part of the profiles.…”
Section: Ecological State Of Wigry Lake-past and Presentmentioning
confidence: 99%
“…Several studies were focused on the anthropopressure on sediments; Warta River studied by Jaskuła and co-authors [10] and Wigry Lake surveyed by Kostka and Leśniak [11], both located in Poland, showed signs of heavy metal pollution. In Warta River, the thirdlongest river in Poland, heavy metal contaminated sediments can act as point sources in urbanized areas and fluvial processes.…”
mentioning
confidence: 99%